Minimal clinically important difference for chest discomfort in patients undergoing pleural interventions - Fabien Maldonado; Greta Jean Dahlberg; Heidi Chen; Otis Rickman; Lance Roller; Charla Walston; James Katsis; Robert Lentz (BMJ Open Respiratory Research)
Rationale Therapeutic thoracentesis is among the most frequently performed medical procedures. Chest discomfort is a common complication and has been associated with increasingly negative pleural pressure as fluid is withdrawn in the setting of non-expendable lung. Visual analogue scales (VASs) are commonly employed to measure changes in discomfort and dyspnoea related to pleural interventions. The minimal clinically important difference (MCID), defined as the smallest change in VAS score associated with patient report of significant change in a symptom, is required to interpret the results of studies using VAS scores and is used in clinical trial power calculations. The MCID for chest discomfort in patients undergoing pleural interventions has not been determined.Methods Prospectively collected data from two recent randomised trials of therapeutic thoracentesis were used for this investigation. Adult patients with symptomatic pleural effusions referred for therapeutic thoracentesis were enrolled across ten US academic medical centres. Patients were asked to rate their level of chest discomfort on 100 mm VAS before, during and following thoracentesis. Patients then completed a 7-point Likert scale indicating the significance of any change in chest discomfort from preprocedure to postprocedure. The mean difference between discomfort 5 min postprocedure and discomfort just prior to the start of pleural fluid drainage was categorised by Likert scale response.Results Data from a total of 262 thoracenteses were included in the analysis. Thirty-four of 262 patients experienced a ‘small but significant increase’ or a ‘large or moderate increase’ in discomfort following thoracentesis. The mean increase in VAS score in those reporting a ‘small but significant increase’ in chest discomfort (n=23) was 16 mm (SD 22.44, 95% CI 6.87 to 25.21).Conclusions The MCID for thoracentesis-related chest discomfort measured by 100 mm VAS is 16 mm. This MCID specific to discomfort resulting from pleural fluid interventions can inform the design and analysis of future pleural intervention studies.